Zastępstwo procesowe Skarbu Państwa. Studium prawno-porównawcze - Sitek, Bronisław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The Act of 15th December 2016 on the General Counsel to the Republic of Poland (Journal of Laws of 2016, item. 2261) has established the new institution in the place of the current General Counsel of the State Treasury. This Act also expanded significantly the scope of competence of this new office also on the administrative and criminal matters, in which there is the interest of the State Treasury. Such a wide legal representation of the rights and interests of the State Treasury is a fairly rare option, at least in Europe. This is a reference to the arrangements being in force during the Second Polish Republic of the twentieth century. These changes are forcing to assess current solutions related to the legal representation of the State Treasury in relation to the solutions found in other European countries. In addition to the legal and comparative approach to the problem, the study will also include a reference to the solutions found in ancient Rome, where the first of this kind office, which was advocatus fisci, was established. The legal and historical research will allow to keep the distance to the current solutions. Thanks to this, it will be possible to identify the optimum model of the State Treasury legal representation.